A review of void formation and its eﬀects on the mechanical performance of carbon ﬁber reinforced plastic - LIU, Xueshu; CHEN, Fei (Engineering Transactions, 2016)
Carbon ﬁber reinforced plastic (CFRP) is ideal for high performance of mechanical properties. However, during the manufacturing process of CFRP, defects or ﬂaws can easily be introduced into the material, among which void is the most common one. Many factors contribute to the formation of void including the curing pressure, resin system, environmental conditions and so on, some of which are almost unavoidable. The presence of voids results in a reduction of the mechanical properties of CFRP, which has been the subject of many researchers for several decades. The aim of this paper is to summarize state-of-the-art studies on void formation and its eﬀects on the mechanical properties of CFRP.